2018
DOI: 10.1111/cpf.12534
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic function is enhanced after peak exercise in endurance‐trained adolescents as well as in their non‐trained controls

Abstract: The aims of the study were to explore the temporal change of cardiac function after peak exercise in adolescents, and to investigate how these functional changes relate to maximal oxygen uptake (VO ). The cohort consisted of 27 endurance-trained adolescents aged 13-19 years, and 27 controls individually matched by age and gender. Standard echocardiography and colour tissue Doppler were performed at rest, and immediately after as well as 15 min after a maximal cardio pulmonary exercise test (CPET) on a treadmil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
(66 reference statements)
2
7
0
Order By: Relevance
“…In a comprehensive meta-analysis including over 14,000 young represented by EF and E/A, were not significantly reduced in our cohort. Whereas Pelliccia et al (26) refer to studies reporting no differences in athletes and non-active controls with an EF being consistently around 50% (58, 59), we report an EF of 66.61 ± 5.77% that corresponds better with the results of recent studies and points towards an improved systolic function in our cohort (3,60,61). The same can be stated for diastolic function with an E/A of 2.46 ± 2.16, which is also similar to findings in the current literature (3,15,61,62).…”
Section: Discussionsupporting
confidence: 77%
“…In a comprehensive meta-analysis including over 14,000 young represented by EF and E/A, were not significantly reduced in our cohort. Whereas Pelliccia et al (26) refer to studies reporting no differences in athletes and non-active controls with an EF being consistently around 50% (58, 59), we report an EF of 66.61 ± 5.77% that corresponds better with the results of recent studies and points towards an improved systolic function in our cohort (3,60,61). The same can be stated for diastolic function with an E/A of 2.46 ± 2.16, which is also similar to findings in the current literature (3,15,61,62).…”
Section: Discussionsupporting
confidence: 77%
“…The effects of exercise on LVFP are controversial. Previous investigations have shown that the E/eʹ ratio, an accurate estimator of LVFP, significantly increased immediately after exercise [36,42,44], while other studies found there was no any change [19,37]. Shave et al suggested, unlike systolic function, temporary reductions in diastolic function were more readily triggered by short and high-intensity exercise [39].…”
Section: Discussionmentioning
confidence: 99%
“…LVEF is a valuable indicator of LV systolic function [20]. Several studies have found increased LVEF immediately after exercise compared to rest [19,37], while another study showed that there was no change in LVEF at 15 min post exercise [36]. Middleton and colleagues [27] observed that increased exercise duration resulted in greater reductions in post-exercise LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…The present meta-analysis observed that peak VO 2 , 6MWT, and QoL were improved by exercise training, as well as FES and IMT. The peak VO 2 may affect oxygen delivery and/or utilization via cardiac, vascular, and skeletal muscle function [33]. Therefore, active skeletal muscle is the major reason to induce the augment of peak VO 2 in HFpEF patients, including oxidative enzyme activity and capillary density [25].…”
Section: Discussionmentioning
confidence: 99%